Using roof borehole electrical resistivity tomography to monitor roof water infiltration in a mine work face - Liang Du; Wenjin Zhu; Lei Wang; Hao Li; Xiaoyu Jiao; Teng Qin (Scientific Reports)
Abstract Roof water inrush in coal mining is a significant type of water-related disaster that usually results from the interconnection of water-bearing geological formations formed by cracks during and after work face mining. Therefore, monitoring roof water infiltration is of paramount importance in preventing or mitigating water inrush in the mine work face. This study employed the roof borehole electrical resistivity tomography method to conduct physical experiments for monitoring water seepage in roof cracks generated during coal model mining. Additionally, roof water infiltration monitoring was performed in the 7130 work face of the Qidong Coal Mine. The results of both physical experiments and field tests demonstrate that roof borehole electrical resistivity tomography (ERT) is well suited for monitoring roof water infiltration in mine work faces, enabling the determination of the temporal and spatial distributions of water seepage. By analyzing the variation patterns of low-resistivity anomalies in the resistivity profile, the water-conducting channels and water outflow points can be identified. Experiments and field tests suggest that the resistivity and its changes are related to the amount of water inflow and water channel. With the increase of water inflow, the relatively low resistivity anomalies region increases, the resistivity value decreases and the water channel appears and expands. With the amount of water inflow decreasing, the relatively low resistivity area becomes smaller, the resistivity value increases, and the water channel narrows or even disappears.Furthermore, by combining the areas of low-resistivity anomalies, a qualitative assessment of the water content can be achieved. Finally, The results of the periodic weighting analysis of the field tests indicate that roof water infiltration is related to periodic weighting. The greater the periodic weighting is, the more severe the roof water infiltration.